The Effect of Rewards, Incentives and Welfare Allowances on Employee Morale at PT. PNM (Independent National Capital) Binjai - Lambok Manurung; Etty Harya Ningsi (Institute of Computer Science (IOCS), 2021)
The research approach used is quantitative, this study uses a questionnaire as a data collection tool which is distributed to 80 employees. The results showed that the reward variable t arithmetic value was 4.227 < t table 1.665 with a significant 0.015 < 0.050, meaning that partially reward had a positive and significant effect on employee morale. The results showed that the Incentive variable t count 1.826 > t table 1.665 with a significant 0.072 > 0.050, meaning that partially the incentive variable had a positive but not significant effect on Employee Morale. The results showed that the Welfare Allowance value t count 2.728 > t table 1.665 with a significant 0.008 < 0.050, meaning that partially the Welfare Allowance variable has a positive and significant effect on Employee Morale. The results showed that the calculated F value was 47,127 with a significant level of 0.00. Because F count 47,127 > F table 2.72 and the significant probability is much smaller than 0.05, i.e. 0.000 < 0.05, the regression model can be said that Rewards, Incentives and Welfare Allowances simultaneously have a positive and significant effect on Employee Morale. While the adjusted R square is 0.637 or 63.7% of the variation in Employee Morale which can be explained by the independent variables Reward, Incentives and Welfare Allowances while the remaining 34.3% (100% - 95.3% = 34.3%) can be explained by other independent variables.